The Effect of Social Media Source Credibility on Purchase Interest of Products from Online Stores - Bela Saskara; Nur Achmad (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Social media marketing is now a dominant business strategy, with many companies using influencers to advertise their products. This study examines the effect of influencer credibility, which includes attractiveness, expertise, and trustworthiness, on consumer purchase intention through the mediation of consumer attitudes. This study uses a quantitative approach with data from 210 respondents collected through a Likert-scale questionnaire. Data analysis was conducted using SEM-PLS through SmartPLS 4.0 software. The results show that influencer credibility has a significant positive impact on consumer attitudes (p-value <0.05, t-statistic > 1.96), and consumer attitudes mediate the relationship between influencer credibility and purchase intention. Dimensions of credibility, such as attractiveness, expertise, and trustworthiness, significantly affect consumer responses to advertisements. Fadil Jaidi is able to convey authentic and relevant messages, thereby increasing consumer trust in JINISO products. This study emphasizes the importance of influencer credibility in building emotional engagement and increasing the effectiveness of digital marketing. These results support previous studies showing that influencer credibility can drive purchase intention through consumer attitudes, making influencers a strategic element in modern marketing communications.